Budaya Literasi Madrasah Ibtidaiyah (Studi Kasus Madrasah Ibtidaiyah Miftahul Ulum Kesamben Wetan Driyorejo Gresik) - Muhamad Arif; Eka Fitriyanti Handayani (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2020)
This is a very pleasant phenomenon, due to the growth of superior seeds in the world of education, which begins with the growing interest in learning among students in elementary schools / madrasah ibtidaiyah. Starting from the exposure to observations and some of the previous studies above, the researcher wanted to conduct specific research, especially on the culture of the school literacy movement, with the theme School Literacy Culture (Case study at Madrasah Ibtidaiyah Miftahul Ulum Kesamben Wetan Driyorejo Gresik). By focusing on two problems. First, about how madrasah ibtidaiyah fosters a literacy culture in students. Second, what are the supporting and inhibiting factors in fostering a culture of literacy at Madrasah Ibtidaiyah Miftahul Ulum Kesamben Wetan Driyorejo. The research method used a qualitative method with a case study approach, observation, interviews and documentation in Madrasah Ibtidaiyah Miftahul Ulum Kesamben Kulon Driyorejo. The data analysis used by researchers was data analysis from Miles and Hubermen, through three stages, condensation data, display data, descriptions and conclusions. From the results of the above discussion, it can be concluded that the development of literacy culture in Madrasah ibtidaiyah Miftahul Ulum Kesamben Driyorejo Gresik. Includes the triology built by madrasah ibtidaiyah, namely: first, the formation of a compulsory reading curriculum (KWB) which is carried out every 15 minutes before learning begins. Second, strengthening the head of madrasah to Human Resources (HR), especially for teachers in guarding the development of a culture of literacy. And third is infrastructure, especially infrastructure in terms of literacy, such as an adequate library, a comfortable reading corner and an abundant book catalog.